Comparison of diagnostic performances of slow-pull suction and standard suction in endoscopic ultrasound-guided fine needle biopsy for gastrointestinal subepithelial tumors - Joon Seop Lee; Chang Min Cho; Yong Hwan Kwon; An Na Seo; Han Ik Bae; Man-Hoon Han (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) is integral to the diagnosis of gastrointestinal (GI) subepithelial tumors (SETs). The impact of different EUS-FNB tissue sampling techniques on specimen adequacy and diagnostic accuracy in SETs has not been fully evaluated. This study aimed to compare the diagnostic outcomes of slow-pull (SP) and standard suction (SS) in patients with GI SETs. Methods In this retrospective comparative study, 54 patients were enrolled. Medical records were reviewed for location and size of the target lesion, FNB needle type/size, technical order, specimen adequacy, diagnostic yield, and adverse events. The acquisition rate of adequate specimens and diagnostic accuracy were compared according to EUS-FNB techniques. Results The mean lesion size was 42.6±36.4 mm, and most patients were diagnosed with GI stromal tumor (75.9%). The overall diagnostic accuracies of the SP and SS techniques were 83.3% and 81.5%, respectively (p=0.800). The rates of obtaining adequate core tissue were 79.6% and 75.9%, respectively (p=0.799). No significant clinical factors affected the rate of obtaining adequate core tissue, including lesion location and size, FNB needle size, and final diagnosis. Conclusions SP and SS had comparable diagnostic accuracies and adequate core tissue acquisition for GI SETs via EUS-FNB.